Song sparrows Melospiza melodia have a home-field advantage in defending against sympatric malarial parasites. Issue 8 (August 2016) - Sarquis-Adamson, Yanina; MacDougall-Shackleton, Elizabeth A.
Abstract : Hosts and parasites interact on both evolutionary and ecological timescales. The outcome of these interactions, specifically whether hosts are more resistant to their local parasites (sympatric) than to parasites from another location (allopatric), is likely to affect the spread of infectious disease and the fitness consequences of host dispersal. We conducted a cross-infection experiment to determine whether song sparrows ( Melospiza melodia ) have an advantage in dealing with sympatric parasites. We captured birds from two breeding sites 437 km apart, and inoculated them with avian malaria ( Plasmodium spp.) cultured either from their capture site or from the other site. Infection risk was lower for birds exposed to sympatric than to allopatric Plasmodium lineages, suggesting that song sparrows may have a home-field advantage in defending against local parasite strains. This pattern was more pronounced at one capture site than at the other, consistent with mosaic models of host–parasite interactions. Home-field advantage may arise from evolutionary processes, whereby host populations become adapted to their local parasites, and/or from ecological interactions, whereby host individuals develop resistance to the local parasites through previous immune exposure. Our findings suggest that greater susceptibility to novel parasites may represent a fitness consequence of natal dispersal.